SÃ”BRE O PERÃODO DE GESTAÃ‡ÃƒO NAS RAÃ‡AS ZEBUINAS: I- RAÃ‡A GUZERAT - Briquet Junior, Raul; Abreu, Jorge de (REVISTA DE AGRICULTURA, 2016)
SÃ”BRE O PERÃODO DE GESTAÃ‡ÃƒO NAS RAÃ‡AS ZEBUINAS: I- RAÃ‡A GUZERAT